Desarrollo de Competencias Emocionales en niños de 4° grado de Básica Primaria en una Institución Educativa del Municipio de Uribía (2023)
The present research aims to address emotional competencies within the framework of what is proposed by Bisquerra and López (2020), who highlight that emotional education seeks to develop emotional competencies, which are considered essential to face the challenges of life and are crucial for the comprehensive growth of the individual's personality; That is why the present study aims to develop emotional competencies in children in the 4th grade of primary school in the educational institution of the Municipality of Uribia la Guajira, since today it is observed that there is little management of emotions on the part of the students. children, a lot of frustration, intolerance and disrespect are being reflected in the classrooms